Comparison of lipid metabolism between broodstock and hybrid offspring in the hepatopancreas of juvenile shrimp (Macrobrachium nipponense): Response to chronic ammonia stress. (20th March 2022) - Li, Yiming; De, Ji; Jiang, Qichen; Yang, Ying; Xu, Wenyue; Du, Xinglin; Zhao, Yunlong
Abstract: Ammonia nitrogen is a major pollutant that causes great physiological harm to crustaceans in culture. In this study, we conducted a 28 day chronic ammonia nitrogen stress experiment with broodstock populations (Dianshan, DS) and hybrid offspring populations (DS ♀ × CD (Changjiang ♂ × Dongting ♀), SCD) exposed to 0, 1 and 10 mg/L of ammonia concentrations. A 28 day feeding trial and chronic ammonia nitrogen stress were used to investigate the effects on the growth performance, histological structure and lipid metabolism of juvenile shrimp, Macrobrachium nipponense . Our results indicated that survival rates in the SCD groups were significantly higher than those in the DS groups, whereas weight and length gain rates were not significantly different between the groups ( p > 0.05). Histological structure results showed that the number of vacuoles in the DS group was significantly higher than that in the SCD group and hepatopancreas cell structures were disrupted in the ammonia treatment groups. The results of oil red staining showed that the number of lipid droplets increased significantly with the increase in ammonia concentration. As the ammonia concentration increased, fatty acid contents, lipid enzyme activities and lipid metabolism‐related gene expression all tended to rise. In conclusion, ammonia nitrogen exposure caused damage to the hepatopancreas structure of juvenile shrimp and disturbed the lipid metabolism of the hepatopancreas. In addition, the SCD population had stronger stress resistance than the DS population when subjected to the same concentration of ammonia nitrogen stress.